Synthesis and luminescence properties of lanthanide complexes incorporating a hydralazine-derived chromophore. - Burton-Pye, B; Heath, S; Faulkner, S (2005)
Reaction of 1-hydrazinophthalazine with chloroacetyl chloride yields 3-chloromethyl-1,2,4-triazolo-phthalazine. Reaction of this product with the tris tert-butyl ester of DO3A yields a triazolophthalazine appended macrocycle. Hydrolysis and complexation with lanthanide ions gives access to a series of lanthanide complexes (Ln = Nd, Eu, Yb, Er); these are all luminescent and exhibit sensitisation of the lanthanide centre by the chromophore.